Janus Kinase Inhibitors as Successful Treatment Alternative in Dupilumab-Induced Psoriasis - Lina Weiss; Corinne Punsap Marbet; Lorenzo Barino Branca; Beda Mühleisen; Alexander Navarini (Karger Publishers, 2024)
Introduction: After the introduction of dupilumab as systemic treatment for atopic dermatitis, an increasing number of patients have been successfully treated. However, reports of patients developing psoriasis as a secondary skin condition have been accumulating. The most likely reason is assumed to be an immune shift from Th2- to Th1-mediated auto-inflammatory processes. Case Presentation: Our patient is a 38-year-old male suffering from head-neck type atopic dermatitis since childhood. As one of the first patients in Switzerland, he received dupilumab in 2018 leading to a significant improvement of his skin lesions. One year later he developed progressing circular erythematous-squamous plaques which correlated histologically with psoriasis. In 2021, 3 years after initiating dupilumab, we switched systemic therapy to baricitinib. Three months after initiation, his psoriatic lesions were completely healed, while the atopic lesions remained stable with low inflammatory activity. Conclusion: In patients treated with dupilumab for atopic dermatitis immune shift needs to be considered in case of newly appearing skin lesions. With a growing number of described cases, we conclude that baricitinib is a good alternative treatment for atopic dermatitis in patients suffering from biologic-induced psoriasis.